Reforming POLITICAL FINANCING in Malaysia - Transparency International-Malaysia (Kuala Lumpur : Transparency International-Malaysia, 2010)
The exercise of democracy in modern political systems has become inseparable from the role that political parties play in popular representation. Today, substantial resources need to be mobilised to participate in the political process, making political parties a dominant force in the political landscape of governance. As a result, political parties have come to exert much influence on society and its institutions, affecting the way democracies function. This has had implications on basic democratic principles such as geographical representation, majority rule through a government of elected representatives and contestation by a diversity of political parties.
Includes bibliographical and indexes.
PSZ_JB PSZ_KL PRZSL MJIIT
Keywords: Campaign funds -- Malaysia; Political campaigns -- Malaysia; Campaign funds -- Law and legislation -- Malaysia; Election law -- Malaysia; Malaysia -- Politics and government